Several diseases that interfere with the differential diagnosis of inflammatory bowel disease - Xia TIAN; Zheng HAN; Xiao-Dong HUANG (Yixue xinzhi zazhi)
A variety of diseases have clinical symptoms, endoscopic manifestations and histo-pathology which are similar to inflammatory bowel diseases (IBD). These can affect its diagnosis and differential diagnosis, and have attracted the attention of doctors in recent years. This article expounds the key points of the related diseases that interfere with the diagnosis of IBD so as to help clinicians im-prove the diagnosis rate and reduce its missed and misdiagnosis diagnosis rates.